Clinical Significance of ST Segment Depression in Lead aVR on ECG as a Predictor of Left Circumflex (LCx) Artery Involvement in Patients of Acute Inferior Wall Myocardial Infarction (Medical Forum Monthly, 2024)
Objective: To determine the diagnostic accuracy of ST depression in aVR lead on electrocardiogram (ECG) in detecting left circumflex artery involvement in inferior wall myocardial infarction taking coronary angiography as gold standard.Study Design: Descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Cardiology, Ch. Pervaiz Elahi Institute of Cardiology, Multan from 13-Aug-2017 to 12-Feb-2018.Materials and Methods: 191 patients with diagnosis of inferior wall MI having age 30-70 years were included in this study. Diagnosis of inferior wall myocardial infarction was made on the basis of ECG, and underwent coronary angiography. Data was analysed through computer software SPSS 20.0. 2×2 contingency table was used to calculate sensitivity, specificity, positive predictive value, negative predictive value of ST depression in aVR taking coronary angiography (CA) as gold standard.Results: Mean age of study patients was 50.49+7.10 years. There were 156 (81.68%) male patients and 35 (18.32%) female patients. There were 79 (41.36%) smokers, 18 (9.42%) patients had positive family history, 111 (58.12%) were hypertensive and 17 (8.90%) patients were dyslipidemic. Sensitivity of ST segment depression in determining the LCx taking coronary angiography as gold standard was 91.8%, specificity 89.4%, positive predictive value (PPV) 75.0% and negative predictive value (NPV) was 96.9%.Conclusion: ST depression in lead aVR has a good sensitivity and specificity (91.8% and 89.4% respectively) in determining the left circumflex artery (LCx) artery involvement in patients of acute inferior wall myocardial infarction.